Molecular Profile of Sensitization to Dermatophagoides Pteronyssinus Dust Mite in Portugal - Limão, R (2022)
Background and objectives: To analyze component-resolved diagnosis of sensitization to Dermatophagoides pteronyssinus (Der p) in patients with respiratory allergy and the association between diagnostic findings and clinical severity in different geographical areas. Methods: The study population comprised 217 patients (mean age, 25.85 [12.7] years; 51.16% female) selected from 13 centers in Portugal (5 from the North, n=65). All had allergic rhinitis with or without asthma and positive skin prick test results to at least 1 dust mite. Specific IgE (sIgE) to Der p, Dermatophagoides farinae, Lepidoglyphus destructor, Der p 1, Der p 2, Der p 10, and Der p 23 was determined using ImmunoCAP. The Mann-Whitney test was applied for the following comparisons: rhinitis vs rhinitis and asthma; mild vs moderate-to-severe rhinitis; North vs South. Results: The prevalence of sensitization was 98.2% for Der p, and 72.4%, 89.4%, 9.7%, and 77% for Der p 1, Der p 2, Der p 10, and Der p 23, respectively. The corresponding median sIgE levels were 8.56, 17.7, 0.01, and 3.95 kUA/L. sIgE to all allergens was higher in patients with moderate-to-severe rhinitis and rhinitis with asthma (nonsignficant). Concentrations of sIgE to Der p 2 were significantly higher in the South than in the North (P=.0496). Conclusion: The most common sensitization in Portugal was to Der p. The highest prevalence and median sIgE level were observed for Der p 2. All sIgE values for molecular components were higher in more symptomatic patients (nonsignificant). Concentrations of sIgE to Der p 2 were higher in the South, probably because of the warmer temperature and/or the larger sample size.